Dominant subtype switch in avian influenza viruses during 2016–2019 in China - Bi, Yuhai; Li, Juan; Li, Shanqin; Fu, Guanghua; Jin, Tao; Zhang, Cheng; Yang, Yongchun; Ma, Zhenghai; Tian, Wenxia; Li, Jida; Xiao, Shuqi; Li, Liqiang; et al. (Nature communications, 2020)
We have surveyed avian influenza virus (AIV) genomes from live poultry markets within China since 2014. Here we present a total of 16,091 samples that were collected from May 2016 to February 2019 in 23 provinces and municipalities in China. We identify 2048 AIV-positive samples and perform next generation sequencing. AIV-positive rates (12.73%) from samples had decreased substantially since 2016, compared to that during 2014–2016 (26.90%). Additionally, H9N2 has replaced H5N6 and H7N9 as the dominant AIV subtype in both chickens and ducks. Notably, novel reassortants and variants continually emerged and disseminated in avian populations, including H7N3, H9N9, H9N6 and H5N6 variants. Importantly, almost all of the H9 AIVs and many H7N9 and H6N2 strains prefer human-type receptors, posing an increased risk for human infections. In summary, our nation-wide surveillance highlights substantial changes in the circulation of AIVs since 2016, which greatly impacts the prevention and control of AIVs in China and worldwide. In this study, the authors present a genomic surveillance of avian influenza genomes sampled from live poultry markets in China. They report that a number of variants have emerged since 2016 that pose an increased risk to humans. They highlight the importance of continuous genome surveillance of circulating influenza strains.